2022
DOI: 10.1097/rli.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Photon-Counting Detector CT for Radiation Dose Reduction for the Assessment of Interstitial Lung Disease in Patients With Systemic Sclerosis

Abstract: Objective: The aim of this study was to determine the potential of photon-counting detector computed tomography (PCD-CT) for radiation dose reduction compared with conventional energy-integrated detector CT (EID-CT) in the assessment of interstitial lung disease (ILD) in systemic sclerosis (SSc) patients. Methods: In this retrospective study, SSc patients receiving a follow-up noncontrast chest examination on a PCD-CT were included between May 2021 and December 2021. Baseline scans were generated on a dual-sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 40 publications
0
30
0
2
Order By: Relevance
“…The latter study even demonstrated 40% less noise for PCD-CT UHR-based temporal bone imaging as compared to comb-filter UHR EID-CT imaging at matching radiation doses and reconstruction settings. 33 A variety of further studies have been published on HR and UHR PCD-CT imaging highlighting its value for lung assessment, 15,25,27,[34][35][36][37][38][39] cardiac imaging 20,24,[40][41][42][43][44] and musculoskeletal applications. 19,33,[45][46][47][48] UHR imaging is of particular interest for these anatomical areas because the clear depiction of fine details may effectively enhance diagnostic accuracy.…”
Section: Translating the Benefits Of Pcd-ct Into Clinical Routine Imp...mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter study even demonstrated 40% less noise for PCD-CT UHR-based temporal bone imaging as compared to comb-filter UHR EID-CT imaging at matching radiation doses and reconstruction settings. 33 A variety of further studies have been published on HR and UHR PCD-CT imaging highlighting its value for lung assessment, 15,25,27,[34][35][36][37][38][39] cardiac imaging 20,24,[40][41][42][43][44] and musculoskeletal applications. 19,33,[45][46][47][48] UHR imaging is of particular interest for these anatomical areas because the clear depiction of fine details may effectively enhance diagnostic accuracy.…”
Section: Translating the Benefits Of Pcd-ct Into Clinical Routine Imp...mentioning
confidence: 99%
“…latest generation) DS EID-CT scanner. 39 In regard to coronary artery imaging, plaque visualization and stent imaging can be improved. 24,40 Two recent studies assessing the UHR scan mode of clinical PCD-CT in patients referred for coronary CT angiography have shown that coronary arteries can be visualized in excellent quality with improved visualization of non-calcified plaque components and with reduced blooming of calcified plaques.…”
Section: Translating the Benefits Of Pcd-ct Into Clinical Routine Imp...mentioning
confidence: 99%
“…Because these preliminary experiences were not designed to investigate the minimum radiation dose necessary for confident ILD evaluation, one can expect to further reduce the dose while maintaining the diagnostic accuracy of PCCT examinations. It is interesting to note that a radiation dose reduction of 66% compared with EID-CT has recently been reported to be is feasible, without penalty in image quality and diagnostic performance in the clinical context of systemic sclerosis 35 . Ultra-low-dose PCCT in vivo used a prototype equipment 9 .…”
Section: Low-dose Uhrmentioning
confidence: 99%
“…Recently, photon counting detectors (PCDs), a new generation of CT detector technology, has been introduced, which offers several advantages compared with previous dual-energy systems enabling high-quality imaging in various medical areas 9–13 with the potential of radiation 14–17 and contrast media dose reduction 18 . Photon counting detectors allow improved spectral separation not only into 2 but several materials, 19 resulting in the possibility of generating virtual noniodine (VNI) images by differentiating between soft tissue, iodine, and calcium.…”
mentioning
confidence: 99%